ABOUT ALGEBRAIC STRUCTURES AND THEIR RANKS - Tadzhimatova Hosiyatkhon Batirjon qizi; Muhiddinova Umidakhon Bahromjon o’gli (International Journal on Integrated Education, 2023)
Concepts of group, ring and field, linear space, concepts of algebra and color of algebra were presented, rules, ideas were reviewed.